Explaining the dimensions of specific competence in training specialist nurses in multiple sclerosis: a qualitative study - Samari Banafshe; Sadeghian Efat; Sattari Mahtab; Aghaie Bahman (Sciendo, 2022)
The complexity of multiple sclerosis (MS) due to psychological, emotional, physical, family, and social dimensions complicates the care of these patients. MS patients need hospitalizations and long-term care to treat and control the progression of the disease. Therefore, the competence of caring for MS patients is one of the important issues in clinical nursing.